Structural modelling of student volleyball athletes’ intimacy, social adjustment, perceived stress, and learning-related anxiety: mediating role of psychological safety - Yishuang Li (BMC Psychology)
Abstract Background Psychological safety is crucial for student-athletes, impacting their stress levels and academic anxiety. Understanding how interpersonal factors like intimacy and social adjustment impact psychological safety can guide interventions to enhance student-athlete well-being. Objectives This study investigates the relationships between intimacy, social adjustment, psychological safety, perceived stress, and learning-related anxiety among student-athletes. It tests explicitly whether psychological safety mediates the effects of intimacy and social adjustment on perceived stress and learning-related anxiety. Methodology A cross-sectional design was employed, involving 300 student-athletes from various universities in Wuhan, China. Participants completed measures of intimacy (RCI), social adjustment (SAS-SR), perceived stress (PSS), learning-related anxiety (LAS), and psychological safety (PSS). Structural Equation Modeling (SEM) was used to analyze direct and indirect relationships among the variables. Results/Discussion The results revealed that intimacy and social adjustment positively impact psychological safety. In turn, psychological safety negatively affects perceived stress and learning-related anxiety. The mediation analysis showed that psychological safety significantly mediates the relationships between both intimacy and social adjustment with perceived stress and learning-related anxiety. Specifically, the study found that higher intimacy and social adjustment levels increased psychological safety, subsequently reducing perceived stress and anxiety levels. These findings underscore the importance of fostering a psychologically safe environment to mitigate stress and anxiety among student-athletes. The study’s implications suggest that coaches and educators should build supportive relationships and enhance social integration to improve psychological safety and overall athlete well-being. Conclusion This study highlights the critical role of psychological safety in student athletes’ mental health. By promoting intimacy and social adjustment, institutions can enhance psychological safety, reduce stress and anxiety, and improve athletes’ academic and personal experiences. Future research should explore longitudinal effects and potential moderators to understand these relationships further.